1981
DOI: 10.1002/iroh.19810660611
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Limiting Plant Nutrient in the Water of Lake Balaton by Algal Assay Procedure

Abstract: llgiil iis~:ty~ were performed on water samples taken from different sites in Lake Baluton. Selcwtstrtcni capricornuturn was used in the test to determine the primarily limiting plant nutrient. The results of siipplementary nutrient additions to the bottle tests were evaluated by cell counts. Thr tests have indicated phosphorus as growth rate limiting, and in two cases a8 biomass limiting plant nutrient, but periodic occ'urrences of nitrogen limitittion cnnnot be excluded. sis of organically bound phosphorus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Dobolyi and Herodek (1980) showed that 32P043-added to water samples was incorporated by living organisms and was neither adsorbed onto suspended solids nor coprecipitated with biogenic lime. Since the amount of P coprecipitating with CaCO, depends on the POd3-concentration, which in turn is held at an extremely low level by the competing planktonic microorganisms, the amount of P coprecipitating with CaCO, may be much less than existing estimates suggest (Istvanovics and Herodek 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Dobolyi and Herodek (1980) showed that 32P043-added to water samples was incorporated by living organisms and was neither adsorbed onto suspended solids nor coprecipitated with biogenic lime. Since the amount of P coprecipitating with CaCO, depends on the POd3-concentration, which in turn is held at an extremely low level by the competing planktonic microorganisms, the amount of P coprecipitating with CaCO, may be much less than existing estimates suggest (Istvanovics and Herodek 1985).…”
Section: Discussionmentioning
confidence: 99%